2018
DOI: 10.3389/fimmu.2018.01457
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hepatic Deposited Immunoglobulin G in the Pathogenesis of Liver Damage in Systemic Lupus Erythematosus

Abstract: The onset of hepatic disorders in patients with systemic lupus erythematosus (SLE) is frequent; however, the etiology and liver pathogenesis of SLE remain unknown. In the present study, the role of hepatic deposited immunoglobulin G (IgG) in SLE-derived liver damage was investigated. From a retrospective analysis of the medical records of 404 patients with lupus and from experimental studies on mice models, we found that liver dysfunction is common in SLE and liver damage with IgG deposition spontaneously deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 51 publications
(56 reference statements)
1
38
0
2
Order By: Relevance
“…Autoantibodies are involved in the pathogenesis of autoimmune diseases (17). Previous studies showed that lupus patient serum induces tissue damage (18)(19)(20). Serum IgG from lupus patients activates inflammatory cells, such as monocytes/macrophages, dendritic cells and neutrophils, which produce cytokines and subsequently induce tissue damage (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies are involved in the pathogenesis of autoimmune diseases (17). Previous studies showed that lupus patient serum induces tissue damage (18)(19)(20). Serum IgG from lupus patients activates inflammatory cells, such as monocytes/macrophages, dendritic cells and neutrophils, which produce cytokines and subsequently induce tissue damage (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated level of serum IgG is a poor prognostic factor for autoimmune hepatitis associated with SLE. Additionally, the deposition of IgG is reported to cause tissue damage [24,25]. The serum IgG levels correlated with the serologic activity and can predict disease ares in patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…15 We previously reported that monocytes/macrophages play an important role in the development of skin and liver inflammation that is induced by IgG deposition. 16,17 Furthermore, we demonstrated that monocytes/macrophage are required for inflammatory arthritis induced by bacterial DNA. 18 However, it remains currently unknown whether and how autoantibody IgG and inflammatory cells contribute to the development of arthritis in SLE, and why bone erosions fail to develop in SLEassociated arthritis.…”
Section: Introductionmentioning
confidence: 87%
“…Monocytes/macrophages are required for the development of skin and liver inflammation induced by lupus IgG. 16,17 Thus, we aimed to determine the role of monocytes/macrophages in the development of arthritis induced by lupus IgG using etoposides which selectively deplete monocytes/macrophages. Monocyte depletion resulted in significantly reduced arthritis in mice ( Figure 3a).…”
Section: Lupus Igg Depositions Cause Arthritis Through Monocytes/macrmentioning
confidence: 99%